MARJOLIN'S ULCER: MALIGNANT TRANSFORMATION FROM BURN SCAR - Prasetyo, Arif Tri; Rizaliyana, Sitti; Saputro, Iswinarno Doso (Jurnal Rekonstruksi dan Estetik, 2018)
Highlights: Marjolin's ulcer can develop into squamous cell carcinoma, typically resulting from chronic scar tissue due. Diagnosis and treatment follow standard malignant lesion protocols, with staging based on UICC classification using histopathological findings. Abstract: Introduction:  Marjolin's ulcer is a malignant lesion from a scar due to burn trauma, chronic osteomyelitis, chronic inflammation, or chronic fistulae. This type of ulcer is rare, usually progressively growing on unhealed wound, accompanied by chronic trauma especially burn scar. Marjolin's ulcer can form different types of pathologies`. Squamous cell carcinoma is the most type of histology. Previously, there was 3 Marjolin's ulcer reported in Indonesia. Case Illustration: Reporting 3 Marjolin's ulcer case on Dr. Soetomo General Academic Hospital since 2008 to 2016. Two patients have history of unhealed chronic wound and one patient has history of burn injury 27 years ago. From the histopathology examination, all the results are squamous cell carcinoma. All patient undergo wide excision surgery done by surgical oncologist. All the defect is closed by flap modality. One patient's defect is closed by latissimus dorsi flap, the other with anterolateral thigh free flap, and the latter is closed by latissimus dorsi free flap. Remain raw surface close by split thickness skin graft. Discussion: Marjolin's ulcer is malignant lesion from scar due to burn trauma, chronic osteomyelitis, chronic inflammation, or chronic fistulae. Marjolin's ulcer sometimes grow become squamous cell carcinoma although require a long time. Treatment this case is same the other malignancy. Diagnosis should be confirmed by clinical, radiological, and pathological. Staging can use the classification of UICC (Union for International Cancer Control) in accordance with the histopathological results.   Conclusion: Surgery serves as the primary approach for achieving local control, and radiotherapy plays a supplementary role, which must be supported by vigilant oncological monitoring.